Design and Simulation of Cam Pressurized CVT - Hao Jianjun; Liu Yunyun; Lan Jiashui; Xiong Feng (Jixie chuandong)
Aiming at the problems of the current CVT actuated by hydraulic control system,such as high energy consumption,complicated control systems,speed ratio and transmission ability being limited by metal belt axial deflection,a new designed cam pressurized CVT hydraulic system is proposed,which is composed of cam automatic pressurized device and closed hydraulic system.The cam pressurized device automatically provides most of the clamping force,the closed hydraulic control system provides the auxiliary clamping force and changes the speed ratio.The new designed hydraulic control system with simple-structure can leave out expensive reversing values and reduce overflow loss,therefore it has advantages of less component parts,energy conservation,environmental protection and low cost.The structure design and working principle of the CVT system are introduced,and the simulation analysis is carried out by using the Matlab/Simulink software.The simulation results show that the cam pressurized CVT hydraulic control system has the significant advantages of fast dynamic response,stable performance and so on.